The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.cdd.4402002
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis is induced in leishmanial cells by a novel protein kinase inhibitor withaferin A and is facilitated by apoptotic topoisomerase I–DNA complex

Abstract: Protein kinase C (PKC) is an important constituent of the signaling pathways involved in apoptosis. We report here that like staurosporine, withaferin A is a potent inhibitor of PKC. In Leishmania donovani, the inhibition of PKC by withaferin A causes depolarization of DW m and generates ROS inside cells. Loss of DW m leads to the release of cytochrome c into the cytosol and subsequently activates caspase-like proteases and oligonucleosomal DNA cleavage. Moreover, in treated cells, oxidative DNA lesions facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 30 publications
4
80
0
1
Order By: Relevance
“…This experiment provides direct and quantitative measurements of the cleavable complex formed in vitro. To understand whether the precipitated count is actually due to topoisomerase I-linked complexes, we performed immunoband depletion assay (12,18). Nuclear extracts were prepared from untreated and treated cells and subjected to SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This experiment provides direct and quantitative measurements of the cleavable complex formed in vitro. To understand whether the precipitated count is actually due to topoisomerase I-linked complexes, we performed immunoband depletion assay (12,18). Nuclear extracts were prepared from untreated and treated cells and subjected to SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, formation of cellular topoisomerase I-DNA cleavable complexes by these compounds do not result from their direct interaction with the topoisomerase I-DNA intermediates. Recently, Sen et al also reported conservation of the apoptotic topoisomerase I-DNA cleavable complex formation by a protein kinase inhibitor, withaferin A, in parasite Leishmania donovani (12). Thus, topoisomerase I-DNA cleavable complexes are implicated directly or indirectly in apoptosis, irrespective of the initiating mechanism or the agent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, besides TRAIL and Fas ligand (present study), Top1cc also form in apoptotic human cells in response to arsenic trioxide (15), staurosporine (16), tubulin and Top2 inhibitors (17, 18), TNF␣ (17), and UV-C radiation (19). Apoptotic Top1cc have also been reported in the parasite Leishmania donovani (42).…”
Section: Discussionmentioning
confidence: 98%